PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PO. BUS NUSANTARA KUDUS (Students' Journal of Economic and Management, 2016)
This research was conducted at PO. Nusantara Kudus due to the phenomena that occur in actual revenue earned PO. Nusantara Kudus from 2012 until 2014 which is not in accordance with the target set by the management PO. Nusantara Kudus. The research objective to analyze the influence of service quality, trust and customer satisfaction corporate image of the PO. Nusantara Kudus. A sample of 100 respondents, using accidental sampling technique that is based on a sampling by chance in distributing questionnaires to passengers PO. Nusantara Kudus. Methods of data analysis using linear regression. The test results showed that there are significant positive and significant correlation between the quality of service to customer satisfaction, there is a positive and significant influence between customer trust to customer satisfaction, and there is a positive and significant influence between perceptions of corporate image on customer satisfaction. Keywords: quality of service, trust, corporate image and customer satisfaction